Doping, drugs and drug abuse among adolescents in the state of Thuringia (Germany): Prevalence, knowledge and attitudes - Wanjek, B.; Rosendahl, J.; Strauss, B.; Gabriel, H. H. (International Journal of Sports Medicine, 2007)
Goal-directed measures to prevent doping and drug abuse in sports requires empirical data. In this connection, a cross-sectional analysis was carried out in 2004. The purpose of the study, on the one hand, was to register reliable data of the current situation in Thuringia, and, on the other hand it was to give information on possible interventional steps with scientific support. Within three months, 2319 adolescents from 16 Thuringian schools (5 regular schools, 4 secondary schools, 3 sport schools and 4 vocational schools) were surveyed. Three hundred and forty-six (15.1 %) students out of 2287 students (26 students without a statement) indicated use of prohibited substances from the WADA list in the previous year [[27]]: 16 (0.7 %) anabolic-androgenic steroids (AAS), 10 (0.4 %) growth hormones, 56 (2.4 %) stimulants, 305 (13.2 %) cannabis, 2 (0.1 %) diuretics, 52 (2.2 %) cocaine/heroin and 6 (0.3 %) erythropoeitin. Moreover, nonathletes (N = 490) reported a substance use that was approximately 5.0 % higher than that of recreational athletes (N = 1254) and nearly three times higher than that of competitive athletes (497). All three groups (nonathletes, recreational athletes and competitive athletes) performed poorly on a knowledge test regarding doping in general with an average below 60 % in each case. Another main aspect of the study was to determine factors influencing substance use in sports. Besides the doping specific knowledge (ß = 0.06, p < 0.05), age contributed (ß = 0.09, p < 0.05), as well as anti-doping attitude (ß = - 0.34, p < 0.05), to the resulting variance. Gender, however, played no role. The findings of the study point towards the need for improvement of specific knowledge of doping among students and that their attitude towards doping must be altered. The goal in this case is to test the effectiveness of appropriate scientific intervention.